Singaraja dan Fragmen-fragmen Relief Penanda Perkembangan Kota Tinjauan Sejarah Visual Awal Abad XX Sebagai Potensi Visual Branding Urban Heritage - Purwita, Dewa Gede (Humanis, 2023)
The relief fragments are interpreted as pieces of relief scattered in the Singaraja City area, viewed from a visual historical point of view in the late 19th to early 20th century. The problem is how to describe the historical narrative of the city through pieces of relief in Singaraja City, which aims to read the flow of the city's development and reveal the potential for visual branding of the cultural heritage of Singaraja City. The research method uses a visual history approach through a qualitative paradigm with analytic descriptive elaboration, the emphasis is more on the 20th century because the remains are based on the distribution of data in the remaining fields, the rest uses literature review and internet data in the elaboration process. Through this research, the narrative of the development of the relief from the medium side and the working technique along with the development of urban culture is obtained due to the multicultural assimilation process which is related to the existence of the city port and the center of government in Singaraja City.